CHEMICAL AND ENZYMATIC SYNTHESIS OF BIOLOGICALLY ACTIVE COMPOUNDS BASED ON BETULIN - Ivshina, I.B.; Tarasova, E.V.; Tolmacheva, I.A.; Grishko, V.V. (Perm Federal Research Centre Journal, 2017)
Biotransformation of polycyclic terpenoids by microorganisms is an efficient method for single- stage production of biologically active compounds with high regio- and stereoselectivity. In the previous studies we have reported about the possible directed transformation of betulin by Rhodococcus actinobacteria to produce pharmacologically valuable betulone. In order to increase the efficiency of the process of biotransformation of betulin, this study focuses on the interactions between rhodococci and hydrophobic triterpene betulin, possible ways of betulin transport into bacterial cells, and the localization of enzymes responsible for betulin oxidation. A detailed study on rhodococci and betulin interactions was performed using a combined system of scanning probe microscopy. The effects of betulin on fatty acid composition of rhodococci and their morphometric and morphofunctional characteristics during biotransformation were studied. A general algorithm of the interactions between bacterial cells and betulin was proposed. New triterpene derivatives with a marked antitumor activity were synthesized based on betulone obtained by a biotechnological method.